2018
DOI: 10.1021/jacs.8b08309
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Charge-Transfer Dynamics in WO3/BiVO4 Photoanodes Probed through Midinfrared Transient Absorption Spectroscopy

Abstract: The dynamics of photopromoted electrons in BiVO 4 , WO 3 and WO 3 /BiVO 4 heterojunction electrodes has been directly probed by transient absorption (TA) mid-infrared (mid-IR) spectroscopy in the picosecond to microsecond time range. By comparing the dynamics recorded with the two individual oxides at 2050 cm-1 with that of the heterojunction system after excitation at different wavelengths, electron transfer processes between selectively excited BiVO 4 and WO 3 have been directly tracked for the first time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 33 publications
7
70
0
Order By: Relevance
“…Besides, transient absorption spectroscopy (TAS), a technique that detects the absorption and thus concentration of photogenerated charge carriers over time, is useful in PEC field as it can map the fates of both photoexcited electrons and holes in photoelectrode . TAS has been utilized in numerous studies to probe the photoexcited charge carrier lifetime and thus the transport and recombination dynamics in photoelectrode materials . Particularly, TAS can provide solid evidence of charge carrier separation and transport in heterojunction by tracking the photoexcited charge carriers on the picosecond to microsecond time scale .…”
Section: Pec Performance and Charge Carrier Dynamic Measurement Technmentioning
confidence: 99%
“…Besides, transient absorption spectroscopy (TAS), a technique that detects the absorption and thus concentration of photogenerated charge carriers over time, is useful in PEC field as it can map the fates of both photoexcited electrons and holes in photoelectrode . TAS has been utilized in numerous studies to probe the photoexcited charge carrier lifetime and thus the transport and recombination dynamics in photoelectrode materials . Particularly, TAS can provide solid evidence of charge carrier separation and transport in heterojunction by tracking the photoexcited charge carriers on the picosecond to microsecond time scale .…”
Section: Pec Performance and Charge Carrier Dynamic Measurement Technmentioning
confidence: 99%
“…These materials are also called type‐II heterojunctions. Several examples of these composites were presented recently, also including titania‐based materials . More specifically, titania can be combined with a metal, graphene, or another oxide .…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of these composites were presented recently, also including titania-based materials. [24][25][26][27] More specifically, titania can be combined with a metal, [28][29][30][31][32][33] graphene, [34,35] or another oxide. [19,20,36,37] Composites can be also created by interfacing two different polymorphs of TiO 2 , [38][39][40][41][42][43] or even two different faces of the same polymorph.…”
Section: Introductionmentioning
confidence: 99%
“…From the aspect of in‐situ analysis of photo‐induced charge dynamics in WO 3 /BiVO 4 heterojunction, Selli et al . developed a technique of transient absorption mid‐infrared spectroscopy in the range of picosecond to microsecond timescale to probe and track the dynamics of photo‐induced charge transfer in WO 3 /BiVO 4 heterojunction . It is demonstrated that the pathway of photo‐induced electron‐transfer process was different when BiVO 4 and WO 3 were selectively excited.…”
Section: Strategies For Enhancing Pec Performancementioning
confidence: 99%
“…From the aspect of in-situ analysis of photo-induced charge dynamics in WO 3 heterojunction. [94] It is demonstrated that the pathway of photo-induced electron-transfer process was different when BiVO 4 and WO 3 were selectively excited. The lifetime of photoinduced electrons of BiVO 4 was obviously prolonged from the magnitude of nanosecond to microsecond when WO 3 /BiVO 4 was excited at 500 nm (Figure 11e).…”
Section: Hetero-/homojunction Fabricationmentioning
confidence: 99%